Increasing community members’ engagement in cancer research: the making research CLEAR program - R. J. Melillo; C. El Khoury; J. Blanding Godbolt; Q. Greene; K. M. Bussard; Amy E. Leader (Research Involvement and Engagement)
Abstract Background Despite the importance of engaging community members in research, multiple barriers from the perspective of the investigator and community member exist. The Making Research CLEAR (Community Learning and Experience about Research) Program aims to bridge the gap between research conducted at an NCI-designated cancer center and the community. Methods Community members and a cancer center investigator were paired for a 6-month immersive research experience. Community members had at least one research experience per month with their investigator, while also attending cancer center activities such as Institutional Review Board (IRB) meetings, research lectures, protocol review meetings, and community outreach events. Community members and investigators completed baseline and endpoint surveys to assess perceptions and impact of the program. Results Seven community member-investigator dyads completed the program. There was strong agreement among community members that participation increased their awareness (Pre M = 4.0, Post M = 4.43) and understanding (Pre M = 3.43, Post M = 4.57) of current cancer research efforts, although there was decreased agreement that their participation would add value to the research (Pre M = 4.71, Post M = 4.57). Community members had increased interest in participating in clinical trials (Pre M = 4.29, Post M = 4.43) and their attitudes towards trials improved (Pre M = 4.57, Post M = 4.71). Their confidence in the safety and benefit of clinical trials was high at baseline (M = 4.71) yet remained unchanged at endpoint. Researchers strongly agreed that the program offered an opportunity to build trust between researchers and community members (Pre M = 4.57, Post M = 5.00) and it improved their understanding of the community’s culture (Pre M = 4.57, Post M = 4.86). Conclusion Overall, measures of community members’ trust and transparency in research and clinical trials increased yet perceptions of their impact on research were mixed. Community input may have limited ability to directly impact the scientific process in a span of 6 months, but researchers’ willingness to partner with community members in the future is promising.